Information Searching Behaviour Patterns of “Swara Pendidikan” Magazine Reporter - Anggraeni, Ayu; Syahri, Moch (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2024)
Reporters of Swara Pendidikan magazine act as information providers in the campus environment. The information provided is categorized as depth news so that the quality of the information depends on its delivery. This study aims to determine the information search behavior patterns of Swara Pendidikan magazine reporters with Meho and Tibo's information search theory. This study uses qualitative research with a descriptive research type. The research data are in the form of sentences from in-depth interviews with research data sources consisting of three people. The results of the study show that Swara Pendidikan magazine reporters have ten similar information search patterns, starting with starting to determine the topic of information sought through the Ministry of Education and Culture website. Chaining, further exploring information sources on the internet. Browsing using Google. Monitoring, monitoring the latest information by matching it to the theme on the Ministry of Education and Culture website. Accessing, rarely encountering obstacles because the network is stable. Differentiating, assessing the content and quality of information by reading it. Extracting, taking important points. Verifying, rereading the information findings. Information managing, using Google Drive and Microsoft Word. Ending with networking to maintain good relationships and report work results. The findings of the information search behavior patterns are slightly different from Meho and Tibo's theory. Differences were found in the networking stage which was carried out after the information managing stage. The findings were based on similarities in information search motivation, tasks and workflows.